L’incendiat juvénile : un phénomène urbain - Ségal, Cécile (Assurances, 1990)
Arson is one of the most difficult crimes to detect, yet its material costs are considerable and it often has a devastating effect on human beings and on society. We would like to thank the author for allowing us to publish her study on arson committed by youths under 18 years of age. This study outlines the main characteristics of arsonists and concludes with effective preventive measures which can be taken. This study, published in April 1989, is a summary of 8 months of research carried out by the author concomittantly with a prevention program drawn up by the Quebec City Fire Department in collaboration with 35 juvenile arsonists.